2011
DOI: 10.1371/journal.pone.0021522
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Trivalent Inactivated Flu Vaccine Using PapMV Nanoparticles

Abstract: Commercial seasonal flu vaccines induce production of antibodies directed mostly towards hemaglutinin (HA). Because HA changes rapidly in the circulating virus, the protection remains partial. Several conserved viral proteins, e.g., nucleocapsid (NP) and matrix proteins (M1), are present in the vaccine, but are not immunogenic. To improve the protection provided by these vaccines, we used nanoparticles made of the coat protein of a plant virus (papaya mosaic virus; PapMV) as an adjuvant. Immunization of mice a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 48 publications
1
55
0
Order By: Relevance
“…immunization, splenic DCs take up PapMV in vivo and acquire a mature phenotype (22). In addition, we recently showed that s.c (34). and intranasal (27) administration of PapMV leads to the production of proinflammatory cytokines and chemokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…immunization, splenic DCs take up PapMV in vivo and acquire a mature phenotype (22). In addition, we recently showed that s.c (34). and intranasal (27) administration of PapMV leads to the production of proinflammatory cytokines and chemokines.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely the result of the direct cross-linking of specific B cell receptors by repeated antigenic patterns found on the surface of PapMV nanoparticles, which could induce Ab production without help from CD4 + T cells. Although some studies have shown that Abs directed toward a vaccine platform can be detrimental to the effectiveness of a recall injection (41), the presence of high levels of Abs against PapMV does not affect the efficacy of a booster vaccination (19,27,34).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the PapMVCP and modified versions of the protein can be produced in bacteria where they self-assemble into nanoparticles in Escherichia coli that resemble the wild-type PapMV virus purified from infected plants. 20 This expression system was used for biochemical investigation of the PapMV CP and also for engineering chimeric recombinant nanoparticles that may be used as adjuvant 21,22 or as a vaccine platform. [23][24][25] PapMV nanoparticles appear to be perceived by the innate immune system as a pathogen-associated molecular pattern.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, preceding titers of specific anti NP IgG can be boosted in only few cases in subjects immunized with conventional trivalent vaccines. 64 In a similar way, Savard et al 66 found that NP and M1 proteins present in split virion seasonal flu vaccine, are not immunogenic in immunized mice. However they showed that immunization of mice and ferrets with the same vaccine adjuvanted with papaya mosaic virus nanoparticles triggered a cell-mediated immune response to NP and M1, and long-lasting protection in animals challenged with a heterosubtypic influenza strain.…”
Section: Are Adjuvanted Split Virus Vaccines Able To Induce a T-cell mentioning
confidence: 85%